Efficient testing of lensless microfluidic imaging system using parallel data transmission - Hou, Junan (2017)
In recent days, with people paying much more attention to their health, the accuracy of disease diagnosis and health assessment becomes more essential. And among all the technology physicians can apply, complete blood count(CBC) tests are swift and widely available, which help a lot with the decision making of physicians[1]. In fact, previous devices applied in a CBC test like the optical microscope and the blood cell analyzer have their crucial drawbacks that they are too heavy and expensive to be widespread. Nor it is impossible for users to carry out the test freely and conveniently. Therefore, a Lensless Microfluidic Imaging System featured a CMOS Image Sensor(CIS) is developed. And Verilog code was designed to control the imaging process of the system. Compared with previous technologies, the newly proposed system is far more convenient and portable. However, although the Lensless Microfluidic Imaging System overcomes the inconvenience of previous devices, quality of the image it generates is strongly influenced by the outside environment because of the series transmission method it applies. When the light condition gets worse, quality of the generated image is non-ideal that it can’t meet the requirement of accurate observation. Thus further improvement is needed to make the Lensless Microfluidic Imaging System have better performance in diverse environments. In this report, a parallel data transmission method of the system was put forward as a substitute for the previous series transmission method. From the comparison made between these two methods, it’s obvious that the new method increases the efficiency of data transmission and have a lower sensitivity to the light condition. Later, the design of the Lensless Microfluidic Imaging system was introduced and the Verilog code with the parallel transmission method is implemented in the system to show its performance.